2022
DOI: 10.21203/rs.3.rs-1486469/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global analysis in non-obstructive azoospermic testis identifies miRNAs critical to spermatogenesis

Abstract: Background The etiology of male infertility accompanied by azoospermia is largely unknown especially at the molecular level. Identifying the global expression profile of dysregulated microRNAs (miRNAs) in male infertility would be useful to achieve a more profound understanding of pathogenesis. Methods Small RNA sequencing was performed on testicular tissues of 10 nonobstructive azoospermic patients with Sertoli cell only syndrome (SCOS) and those of 8 obstructive azoospermic individuals. The expression of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, the miRNA/mRNA axis has been considered an effective functional marker in various biological processes including spermatogenesis 5 – 8 . In particular, several studies have indicated that the miR-34b family has a crucial role as a regulatory factor on genes involved in spermatogenesis 9 11 . This family of miRNAs is highly conserved among species that involve different biological procedures including differentiation, growth, cell cycle, spermatogenesis, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the miRNA/mRNA axis has been considered an effective functional marker in various biological processes including spermatogenesis 5 – 8 . In particular, several studies have indicated that the miR-34b family has a crucial role as a regulatory factor on genes involved in spermatogenesis 9 11 . This family of miRNAs is highly conserved among species that involve different biological procedures including differentiation, growth, cell cycle, spermatogenesis, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…5% of men have infertility, of which 75% are said to have idiopathic sperm dysfunction of unknown cause (Okada et al, 2008). The miR888 cluster was downregulated in the testis of non-obstructive azoospermia (NOA) patients compared to obstructive azoospermia patients (Piryaei et al, 2022). Misexpression of target genes due to Fx-mir downregulation is thought to impair spermatogenesis, and Fx-mir and its target genes may be candidates for DMI model genes.…”
Section: Infertilitymentioning
confidence: 99%